The Influence of Perceived Ease of Use, Perceived Usefulness, Enjoyment and Subjective Norms on Satisfaction with Customer Experience Through Brand Engagement for Sephora Application Users in Surabaya - Njoo Dylan Young; Janice Carysa Siahaya (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study aims to examine the effect of Perceived Ease of Use, Perceived Usefulness, Enjoyment, and Subjective Norms on customer experience satisfaction through brand engagement for Sephora application users in Surabaya. This study uses quantitative methods with data collected from 130 respondents who are active users of the Sephora application. Data processing was carried out using SPSS software to analyze the relationship between variables through multiple linear regression tests. The results showed that Perceived Ease of Use, Perceived Usefulness, Enjoyment, and Subjective Norms have a significant influence on brand involvement, which then affects the level of customer satisfaction in using the Sephora application. Enjoyment and Perceived Usefulness factors are shown to be the main predictors that influence brand engagement and user satisfaction. These findings provide insights for companies in optimizing factors that can enhance customer experience through strong brand engagement.